THE EFFECT OF INCUBATION PERIOD ON ETHANOL CONTENT OF JASMINE AND GREEN TEA KOMBUCHA - Ihsani, Nisa; Hernahadini, Nelis; Nurissalma, Zahra Salsabila; Nurul Huda, Annisa; Sartika, Tiwi; Nadya Nur Afifah , Arifa Nadya Nur Afifah; Rahma Nur Syamsiyah, Ninda (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2023)
Kombucha is a fermented tea that provides many benefits for health. The alcohol (ethanol) content of kombucha has withdrawn a lot of attention because of human health risks and halal concerns. Alcohol and Tax and Trade Bureau (TTB), BC Center for Disease, and MUI fatwa have defined that kombucha is safe to be consumed as long as the alcohol content is less than 0.5%. This study was conducted to compare the alcohol (ethanol) concentration of jasmine and green tea kombucha during the fermentative stage (5 day at 25oC) and post-fermentative stage (7 and 21 day, both at 4oC). The result showed that ethanol concentrations for jasmine and green tea kombucha rose from the fifth d of incubation to the seventh d of the post-fermentative stage, followed by a decline at 21th d of the post-fermentative stage (p>0.05). The level of organic acids, Acetic Acid Bacteria (AAB), and pH confirmed that there were no significant differences at all (p>0.05). In conclusion, jasmine and green tea kombucha at fermentative stage (5 d at 25oC) and post-fermentative stage (7 and 21 day, both at 4oC) did not produce ethanol more than 0.5%, without any significant differences in organic acids and AAB levels, respectively.